2012
DOI: 10.1038/bjc.2012.17
|View full text |Cite
|
Sign up to set email alerts
|

Pre-treatment lactate dehydrogenase levels as predictor of efficacy of first-line bevacizumab-based therapy in metastatic colorectal cancer patients

Abstract: Background:Lactate dehydrogenase (LDH) represents a predictive factor in colorectal cancer patients treated with the angiogenesis inhibitor PTK/ZK. We explored the role of pre-treatment LDH serum levels in colorectal cancer patients receiving first-line bevacizumab.Methods:Metastatic colorectal cancer treated with first-line bevacizumab was eligible. A control group including all consecutive patients treated with chemotherapy alone was also considered. Pre-treatment LDH serum levels were collected for all case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
93
2
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(102 citation statements)
references
References 21 publications
(22 reference statements)
5
93
2
2
Order By: Relevance
“…LDH is a metabolic enzyme that catalyzes the conversion of pyruvate to lactate under anaerobic conditions and is overproduced in cancer cells [8]. Several studies have demonstrated a negative association between elevated LDH and OS [9][10][11]. CEA is a glycoprotein involved in cell adhesion, immunity and apoptosis [12].…”
Section: Introductionmentioning
confidence: 99%
“…LDH is a metabolic enzyme that catalyzes the conversion of pyruvate to lactate under anaerobic conditions and is overproduced in cancer cells [8]. Several studies have demonstrated a negative association between elevated LDH and OS [9][10][11]. CEA is a glycoprotein involved in cell adhesion, immunity and apoptosis [12].…”
Section: Introductionmentioning
confidence: 99%
“…Similar results have been communicated in patients diagnosed of advanced Non-Small Cell Lung Cancer (NSCLC) [20], were a significantly poorer survival was noted in the group of patients with high LDH5 immunohistochemical reactivity, both when measured at cytoplasm and at nucleus. In addition, Scartozzi et al observed similar findings in patients with high LDH serum levels [21], who presented a significant shorter PFS (4.2 vs. 8 months, p=0.003) and OS (19.6 vs. 34.9 months, p=0.0014), when compared with patients with low LDH levels in serum. Despite all this data, in our series the high expression of LDH5 was not associated with classical clinical factors associated with worse prognostic features, such as loss of weight, bad performance status or more than one metastatic site.…”
Section: Discussionmentioning
confidence: 61%
“…Previous reports found similar results regarding to the better outcome of patients with overexpression of pro-angiogenic proteins when treated with Bevacizumab. Both patients with high levels of pKDR measured by immunohistochemistry, and patients with high serum level of LDH presented a benefit in RR, PFS and OS, when compared with patients with high expression of these markers and treated with chemotherapy alone [21,22]. All these experiences show that the addition of bevacizumab to chemotherapy permits to improve clinical outcome in a subgroup of patients who usually present with an adverse natural history.…”
Section: Discussionmentioning
confidence: 91%
“…Accordingly with these observations we previously suggested that pre-treatment LDH levels may represent a relevant factor for the prediction of bevacizumab efficacy in an unselected population of CRC patients [13].…”
Section: Introductionmentioning
confidence: 71%